DEVELOPMENT OF ECOPEDAGOGICAL EDUCATIONAL MECHANISMS FOR STUDENTS OF HIGHER EDUCATION ORGANIZATIONS - Murtоzaeva Makhfuza Murtozaevna (Journals Park Publishing, 2024)
In the article there considered the issues of development of education as important factor in maintenance of ecological stability in the conditions of further deepening of democratic reforms and development of civil society. Also, materials related to ecopedagogy, and analyzes focused on scientific conclusions are highlighted. Opinions were expressed that students and young people should study the direct connection between man-nature-society, its place in the social society, and in this process should be an active citizen in protecting the environment.
Keywords: Ecology, ecopedagogy, education, stability, safety, development.